2001
DOI: 10.1037/0022-3514.80.2.268
|View full text |Cite
|
Sign up to set email alerts
|

The dyadic nature of social information processing in boys' reactive and proactive aggression.

Abstract: The correlation between boys' social cognitions and their aggressive behavior toward peers was examined as being actor driven, partner driven, or dyadic relationship driven. Eleven groups of 6 familiar boys each (N = 165 dyads) met for 5 consecutive days to participate in play sessions and social-cognitive interviews. With a variance partitioning procedure, boys' social-cognitive processes were found to vary reliably across their dyadic relationships. Furthermore, mixed models regression analyses indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(224 citation statements)
references
References 37 publications
(60 reference statements)
11
201
0
12
Order By: Relevance
“…Dodge, Lochman, Harnish, Bates, and Pettit (1997) studied aggression in youth and found reactive aggressive youth to have inadequate problem-solving coping patterns. Hubbard, Dodge, Cillessen, Coie, and Schwartz (2001) also noted that social-cognitive processes in relationships were an important factor in boys' aggressive behavior. It has been noted that there is no difference in the amount of anger experienced or expressed due to gender (Yarcheski, Mahon, & Yarcheski, 2002), while others have found that females reported higher levels of internal anger expression (Lamb, Puskar, Sereika, Patterson, & Kaufmann, 2003) and males possess higher levels of anger in other areas, specifically outward anger and angry reaction (Guimaraes & Pasian, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dodge, Lochman, Harnish, Bates, and Pettit (1997) studied aggression in youth and found reactive aggressive youth to have inadequate problem-solving coping patterns. Hubbard, Dodge, Cillessen, Coie, and Schwartz (2001) also noted that social-cognitive processes in relationships were an important factor in boys' aggressive behavior. It has been noted that there is no difference in the amount of anger experienced or expressed due to gender (Yarcheski, Mahon, & Yarcheski, 2002), while others have found that females reported higher levels of internal anger expression (Lamb, Puskar, Sereika, Patterson, & Kaufmann, 2003) and males possess higher levels of anger in other areas, specifically outward anger and angry reaction (Guimaraes & Pasian, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance and specificity of the interpersonal context was examined by Hubbard, Dodge, Cillessen, Coie, and Schwartz (2001), who observed 11 groups of six boys interact with each other in contrived peer groups on a daily basis for 5 consecutive days. In between play sessions, boys responded to hypothetical provocations involving each of their peer group members.…”
Section: Social Psychology: Nonrational Attributionsmentioning
confidence: 99%
“…Although studies usually report a high correlation between reactive and proactive aggression (mean r=0.68; Card and Little 2006), factor analyses and meta-analyses provide clear evidence for the validity of the distinction between the two functions of aggression (Card and Little 2006;Crick and Dodge 1996;McAuliffe et al 2007;Poulin and Boivin 2000;Vitaro et al 1998). As will be discussed in more detail below, evidence also suggests that these two functions of aggressive behavior are differentially related to social cognitive skills, particularly with respect to the decoding of social stimuli (Crick and Dodge 1996;Dodge et al 1997;Dodge and Coie 1987;Hubbard et al 2001;Schippel et al 2003). The present study examines a specific and as yet unstudied aspect of decoding-related social cognitive skills, namely theory of mind, in relation to proactive and reactive aggression.…”
mentioning
confidence: 99%